Technical guidance for the production of sorghum (Sènèkèlaw sènè kètiogo gnouma de bè sôrôdjidi) - International Institute of Tropical Agriculture (International Livestock Research Institute, 2018)
Episode three of a radio program series by the Africa RISING program in Bambara dialect that is spoken in southern Mali. In this episode which aired on KAFO KAN radio on 03 November 2017, farmers are being provided with relevant technical information about how to grow the best sorghum – starting from land preparation to the good agricultural practices. This radio program was produced as part of Africa RISING activity – Use of Interactive radio to scale-up agriculture and nutrition technologies in Africa RISING Mali.